PARLIAMENT SEPTEMBER, 1939 (Historia, 2021)
The Sunday Times has carried two authoritative articles about the events in Parliament when war broke out in 1939. On August 2, 1964, Mr. Harry Lawrence, who was then the only surviving member of the crisis Cabinet, wrote a detailed account of the Cabinet meeting at Groote Schuur on Sunday, September 3. He also described what took place in the House of Assembly the following day. On September 5, 1965, Mr.Leslie Blackwell, who represented Kensing-ton constituency in 1939, wrote an account of the decisive battle between Generals Hertzog and Smuts in the House of Assembly en September 4, 1939. He made one error; the Senate expired on September 5, not September 6, 1939 as he said.
Keywords: General Hertzog; Parliament; Blackwell, L.; Nicholls; General Smuts; Lawrence, H